2016
DOI: 10.1038/cddis.2015.407
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-suppressive function of long noncoding RNA MALAT1 in glioma cells by downregulation of MMP2 and inactivation of ERK/MAPK signaling

Abstract: Metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) is a type of long noncoding RNA. It is associated with metastasis and is a favorable prognostic factor for lung cancer. Recent studies have shown that MALAT1 plays an important role in other malignancies. But, little is known about the role of MALAT1 in glioma. In this study, quantitative reverse transcription PCR (qRT-PCR) was used to demonstrate that the expression of MALAT1 was lower than that in normal brain tissues. Stable RNA interference-me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
155
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(164 citation statements)
references
References 36 publications
7
155
0
Order By: Relevance
“…And downregulation of MALAT1 affects proliferation and the expression of stemness markers in glioma stem cell line SHG139S [30]. In addition, the potential employment of lncRNAs as novel biomarkers is supported by widespread observations [31]. Previous study has indicated the promotive roles of MALAT1 in gastric tumor [9], here we further confirmed this idea and showed that overexpression of MALAT1 could attenuate or even reverse the inhibitory effects of UPF1 on gastric tumor.…”
Section: Discussionsupporting
confidence: 76%
“…And downregulation of MALAT1 affects proliferation and the expression of stemness markers in glioma stem cell line SHG139S [30]. In addition, the potential employment of lncRNAs as novel biomarkers is supported by widespread observations [31]. Previous study has indicated the promotive roles of MALAT1 in gastric tumor [9], here we further confirmed this idea and showed that overexpression of MALAT1 could attenuate or even reverse the inhibitory effects of UPF1 on gastric tumor.…”
Section: Discussionsupporting
confidence: 76%
“…Compared with the CC genotype, the CT and TT genotypes both increased the risk of T-ALL. MMP-2 is one of the factors in the MMP family that is closely associated with tumor progression [31, 32]. In addition to the degradation of type IV collagen in the basement membrane, MMP-2 interacts with other biologically active molecules, such as growth factors binding proteins and growth factor receptors [33].…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs are closely associated with tumor development (9,10) and particularly, have been implicated in glioma progression (11). For example, the lncRNA, MALAT1, has been demonstrated to have crucial roles in the cell proliferation, metastasis and apoptosis processes in glioma (12)(13)(14). MALAT1 was proposed as a tumor suppressor in glioma (14).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the lncRNA, MALAT1, has been demonstrated to have crucial roles in the cell proliferation, metastasis and apoptosis processes in glioma (12)(13)(14). MALAT1 was proposed as a tumor suppressor in glioma (14). Knockdown of MALAT1 increases the blood-tumor barrier permeability (15), and affects proliferation and the expression of stemness markers in glioma (12).…”
Section: Introductionmentioning
confidence: 99%